Silencing of HEATR1 contributes the synergistic effect of Feiyanning decoction and cisplatin on the inhibition of cell viability in A549/DDP cells - Zhongchao Mai; Guoyu Wang; Xing Ma; Borong Zhou; Xinlin Yang; Menghan Wang; Wei Xia (All Life, 2022)
Lung cancer is the most common malignant cancer in the world, and non-small cell lung cancer (NSCLC) accounts for about 85% of all lung cancer cases. Presently, chemotherapy is the main treatment, but the therapeutic effect is not satisfactory due to drug resistance. Feiyanning decoction (FYN), a widely used Chinese Tradition Medicine (TCM), shows a good effect on the treatment of lung cancer. However, the underlying mechanism seems unclear. In this study, FYN was applied to cisplatin-resistant A549 cell line. Cell viability and apoptosis were detected by cell counting kit 8 (CCK-8) and Annexin V/PI kit. Xenograft mouse model was constructed to analyze the tumor growth. The results showed that FYN inhibited cell viability and promoted cell apoptosis in a dose-dependent manner. Downregulated of Bcl-2 and upregulated of HEATR1, TAp73, p53 and Bax were observed after treatment with FYN. Interestingly, all these effects induced by FYN were alleviated by HEATR1 overexpression in A549/DDP cells. Furthermore, FYN played a synergistic effect with cisplatin on the increase of cell apoptosis in vitro and the inhibition of tumor growth in vivo. In conclusion, FYN played a synergistic effect with cisplatin on the inhibition of cell viability in NSCLC via negatively regulating HEATR1.